TMIC-62. FYN, AN EFFECTOR OF ONCOGENIC RECEPTOR TYROSINE KINASES SIGNALING IN GLIOBLASTOMA, INHIBITS ANTI-GLIOMA IMMUNE RESPONSES: IMPLICATIONS FOR IMMUNOTHERAPY. (11th November 2019) - Comba, Andrea; J Dunn, Patrick; E Argento, Anna; Kadiyala, Padma; Ventosa, Maria; Patel, Priti; Zamler, Daniel; Nunez, Felipe; Zhao, Lili; Castro, Maria; Lowenstein, Pedro
Abstract: There is currently much excitement for the use of immunotherapies in cancer. In spite of positive results using checkpoint inhibitors in melanoma and CAR T cells in leukemias, these strategies have not yet achieved robust clinical responses in human gliomas. A powerful inhibitory microenvironment is thought to be the culprit. Mechanisms that determine the inhibitory microenvironment remain poorly understood. Herein we demonstrate that FYN, a downstream target of receptor tyrosine kinases signaling, inhibits the anti-glioma immune response. We utilized genetically engineered mouse models (GEMM) of glioma based on the Sleeping Beauty Transposon method. We examined the activities of FYN in NP (N-ras + shp53), NPA (NP + shATRX), and NPD (NP + PDGF overexpression) tumors. We also generated FYN knockdown glioma stem cells in vitro to induce gliomas in immune-competent and immune-deficient mice of varying genetic backgrounds (NSG, CD8-/-). Flow cytometry was used to characterize immune cells within the glioma microenvironment. Our results show that FYN knockdown in NP, NPA, or NPD GEMM of glioma reduced tumor progression and increased survival by 25–77%. GSEA analysis of differential expressed genes of WT vs. FYN knockdown gliomas revealed enrichments of gene ontologies related to immune functions. In NSG and CD8-/- immune-deficient mice, FYN knockdown failed to inhibits tumor growth and increase animal survival. These results suggest that FYN enhances tumor progression through changes in anti-glioma immune activation. Examination of tumor immune infiltrates by flow cytometry indicate a 50–70% reduction in powerful immune inhibitory myeloid derived cells (MDSCs) with no changes in the total level of CD8+ and CD4+ cells. Our results show for the first time that FYN reduces anti-glioma immune responses, likely through a reduction in inhibitory MDSCs. The specific inhibition of FYN exclusively within glioma cells, could improve the efficacy of anti-glioma immunotherapies.